HUBUNGAN DUKUNGAN SOSIAL DENGAN KESEJAHTERAAN PSIKOLOGIS MAHASISWA ASING UIN RADEN FATAH PALEMBANG - Sonia Fijri; Manah Rasmanah; Hartika Utami Fitri (Ensiklopedia Education Review, 2026)
This study, entitled "The Relationship between Social Support and Psychological Well-Being of International Students at UIN Raden Fatah Palembang," aims to determine the relationship between social support and the psychological well-being of international students at UIN Raden Fatah Palembang. This study employed a quantitative correlational method. The sample size was 41 respondents, and the sampling technique used was non-probability sampling with saturated sampling. This study employed prerequisite tests, including normality, linearity, and hypothesis testing, using SPSS. Data collection was conducted using a questionnaire. The results showed that rxy = 0.521 with a significance level of 0.000 (p 0.01). This indicates a positive relationship between social support and the psychological well-being of international students at UIN Raden Fatah Palembang. This relationship indicates that higher social support leads to higher psychological well-being, while lower social support leads to lower psychological well-being of international students.Keywords: social support, psychological well-being, international students.